Nikkomycin Z counteracts Rylux BSU and Congo red inhibition of Saccharomyces cerevisiae growth but does not prevent formation of aberrant cell walls - Raclavský, V; Novotný, R; Smígová, J; Vojkůvka, Z (Folia microbiologica, 1999)
Rylux BSU and congo red bind to chitin, interfere with proper cell-wall assembly, and stimulate chitin synthesis by increasing, most probably, chitin synthase 3 (ChS3) levels in Saccharomyces cerevisiae. On the other hand, the antibiotic nikkomycin Z inhibits chitin synthesis competitively. As ChS3 is the critical target of nikkomycin Z, its effect was tested in cells inhibited in growth by Rylux BSU or Congo red. Nikkomycin Z counteracted this inhibition but did not counteract aberrant cell-wall formation. These results indicate that chitin synthesis stimulation is the key step in Rylux BSU and congo red inhibition and support the idea that increase in chitin synthesis represents a compensatory response to damaged cell-wall structure. As Rylux BSU and congo red bind to newly synthesized chitin, further damage is caused in the wall and the response works in this case contrariwise. Nikkomycin Z breaks this vicious circle by counteracting the chitin synthesis stimulation.
Keywords: Chitin; Coloring Agents; Microscopy, Electron; aminoglykosidy; Benzenesulfonates; Kongo červeň; antibakteriální látky; fluorescenční barviva; Fluorescent Dyes; Anti-Bacterial Agents; Aminoglycosides; barvicí látky; Saccharomyces cerevisiae; Congo Red; buněčná stěna; elektronová mikroskopie; Cell Wall; chitin; benzensulfonáty